Determinants of Customer Loyalty Towards E - Tailers in India : An Empirical Study - Rao, Akshat Aditya; Kothari, Rajesh (Indian Journal of Marketing, 2017)
Purpose : This paper attempted to identify the factors responsible for e-loyalty among online shoppers in India. The study was mainly focused on online shoppers residing in tier I and II cities of India. Research Methodology : A structured questionnaire was developed with the help of previous literature on customer loyalty in e-commerce. This was mainly guided by the study of Srinivasan, Anderson, and Ponnavolu (2002). A survey method was adopted to collect data from the respondents actively engaged in online shopping. The study involved usage of exploratory factor analysis, ordinary least square (OLS), t - test, and ANOVA to gauge the significant variables driving customer e-loyalty. Research Findings : The present study documented five significant variables that affected e-loyalty of online shoppers in India. These are Choice, Community, Cultivation, Convenience, and Character. The research also exhibited variation in e-loyalty across the demographic variables. Contribution : The present study contributes to extant literature by bridging the gap between theory and practice. It also guides Indian e-tailers by suggesting imperative factors and their relationship with e-loyalty.